2008
DOI: 10.1094/cchem-85-5-0654
|View full text |Cite
|
Sign up to set email alerts
|

Oat Grain Density Measurement by Sand Displacement and Analysis of Physical Components of Test Weight

Abstract: Test weight or bulk density of oats (Avena sativa L.) has a major influence on the monetary value of oat grain. We hypothesize that test weight can be attributed to grain density and packing efficiency. We have measured oat grain volume and density by a sand‐displacement method and derived the packing factor for six oat cultivars grown in three environments. Volumes of individual grains were 31–38 mm3 and were highly correlated with grain mass. Grain densities were 0.96–1.03 g/cm3. Packing efficiency, defined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
2
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 12 publications
3
14
2
3
Order By: Relevance
“…Previous studies have demonstrated that the combination and interactions of individual particle shapes in mixtures has an effect on the packing characteristics and bulk density of grains (Boac et al, 2010;Doehlert and McMullen, 2008). While the statistical contribution of unilateral and bilateral shape in this study was moderate, the analysis was constrained by the relative quantities of each shape produced naturally during popping; the preponderance of unilateral flakes varied from 1.13 to 23.5%, percent bilateral ranged from 19.6 to 54.7%, and multilateral ranged from 30.5 to 68.0% across all runs in this study.…”
Section: Relationship Of Shape To Expansion Volumementioning
confidence: 99%
“…Previous studies have demonstrated that the combination and interactions of individual particle shapes in mixtures has an effect on the packing characteristics and bulk density of grains (Boac et al, 2010;Doehlert and McMullen, 2008). While the statistical contribution of unilateral and bilateral shape in this study was moderate, the analysis was constrained by the relative quantities of each shape produced naturally during popping; the preponderance of unilateral flakes varied from 1.13 to 23.5%, percent bilateral ranged from 19.6 to 54.7%, and multilateral ranged from 30.5 to 68.0% across all runs in this study.…”
Section: Relationship Of Shape To Expansion Volumementioning
confidence: 99%
“…Physical characteristics of grain resistant to dehulling, including bulk density, mean kernel mass, mean kernel volume, mean kernel density, mean groat mass, mean groat volume, mean groat density, mean hull mass, mean hull volume, mean hull density, oat kernel length, kernel width, and kernel image area were determined as described in detail earlier (Doehlert and McMullen 2008).…”
Section: Analysesmentioning
confidence: 99%
“…The trend for kernel density in resistant oats with increasing rotor speed was the opposite of that of the bulk density. The changes in bulk density must be attributed to differences in packing efficiency of the oats resistant to dehulling, since bulk density is defined as the product of kernel density and packing efficiency (Doehlert and McMullen 2008;Doehlert et al 2009a). Packing efficiency was much lower in all fractions of resistant oats, and their values decreased as rotor speed was increased.…”
Section: Oats Resistant To Dehullingmentioning
confidence: 99%
“…El PH ha sido una determinación empleada internacionalmente para reflejar la calidad física del grano de avena (Forsberg & Reeves, 1992), utilizada como estándar en la clasificación de granos y como una primera herramienta de selección de calidad. Por definición es la masa de granos que entra en un volumen específico, por lo tanto no solo depende de la densidad media del grano sino también de la eficiencia del empaquetado (Doehlert & McMullen, 2008). Valores altos no solo determinan que una mayor cantidad de grano se pueda transportar o almacenar, sino que también es una de las características deseables para la molienda, ya que está relacionado con la mejora en la eficiencia de descascarado y una mayor producción de copos de avena (Doehlert & Wiessenborn, 2007).…”
Section: Estructura Y Composiciónunclassified
“…Además, se identificaron dos genotipos (Calén y Milagros) con tendencia a formar espiguillas triples. Trabajos realizados por Doehlert et al (2004), Doehlert et al (2008), y Brunava & Alsina (2015), mencionan genotipos con esta característica. Por último, este carácter se encuentra influenciado por el ambiente, ya que la mejora en las condiciones de llenado en 2015, permitieron el cuaje de un tercer grano en ciertos genotipos.…”
Section: Porcentaje De Cariopses Y Porcentaje De Proteina"unclassified